2005
DOI: 10.1007/s00270-004-0171-9
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Repair of Abdominal Aortic Aneurysms: Analysis of Aneurysm Volumetric Changes at Mid-Term Follow-Up

Abstract: The lack of volume decrease in the aneurysm of at least 0.3% at 6 months follow-up indicates the need for closer surveillance, and has a higher predictive accuracy for an endoleak than Dmax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 43 publications
1
37
0
3
Order By: Relevance
“…Al contrario, un incremento dimensionale della sacca è associato ad un aumentato rischio di rottura e necessita pertanto di trattamento [14][15][16][17][18][19]. L'analisi volumetrica della sacca consente un più accurato monitoraggio degli aneurismi dell'aorta addominale (AAA) sottoposti ad EVAR rispetto alle comuni misurazioni lineari; diversi studi hanno infatti evidenziato come non sempre le variazioni del diametro massimo rappresentino correttamente le reali modifiche dimensionali dell'aneurisma [14,15,[20][21][22]. Il diametro infatti è l'espressione del cambiamento lineare dell'aneurisma, mentre la valutazione del volume della sacca esprime la variazione dimensionale in tutti i piani dello spazio [14].…”
Section: Discussioneunclassified
See 2 more Smart Citations
“…Al contrario, un incremento dimensionale della sacca è associato ad un aumentato rischio di rottura e necessita pertanto di trattamento [14][15][16][17][18][19]. L'analisi volumetrica della sacca consente un più accurato monitoraggio degli aneurismi dell'aorta addominale (AAA) sottoposti ad EVAR rispetto alle comuni misurazioni lineari; diversi studi hanno infatti evidenziato come non sempre le variazioni del diametro massimo rappresentino correttamente le reali modifiche dimensionali dell'aneurisma [14,15,[20][21][22]. Il diametro infatti è l'espressione del cambiamento lineare dell'aneurisma, mentre la valutazione del volume della sacca esprime la variazione dimensionale in tutti i piani dello spazio [14].…”
Section: Discussioneunclassified
“…I nostri risultati possono essere spiegati dalla migliore qualità delle immagini, ottenute con tomografo a 64 strati, rispetto ai lavori precedenti che hanno utilizzato apparecchi meno performanti ( [14,15,[20][21][22]. Diameter is the expression of a linear change in only a single crosssection, whereas volume changes involve the aneurysm in all space dimensions [14].…”
Section: Discussioneunclassified
See 1 more Smart Citation
“…Traditionally, the preferred imaging method for surveillance of EVAR of AAA is CT angiography, which involves a series of maximal diameter measurements of the aneurysm at regular periods of follow-up, and determining whether the aneurysm is shrinking, enlarging, or remaining unchanged. This has been challenged by some studies which demonstrated the inaccuracy of diameter measurements [36][37][38] . Studies showed that volume measurement is superior to diameter measurement as it reflects all size changes of the aneurysm [37,38] .…”
Section: D Image Visualizationsmentioning
confidence: 95%
“…This has been challenged by some studies which demonstrated the inaccuracy of diameter measurements [36][37][38] . Studies showed that volume measurement is superior to diameter measurement as it reflects all size changes of the aneurysm [37,38] . Thus, accurate evaluation of the aneurysm and stent grafts relative to the aortic branches cannot be assessed based only on 2D axial images.…”
Section: D Image Visualizationsmentioning
confidence: 95%